Development of Discrete Power Supply with Charge Pump Method for High Powered Sonar System - Kristian Ismail; Syamsu Ismail (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2012)
Power supply is one of the electronic devices that can provide electric energy for electronic systems or other systems. There are several types of power supplies that can be applied depend on the requirement and functions. One example is the use of power supply for sonar systems. Sonar system is a device which can be used to detect a target under water. The sonar system is an electronic circuit that requires a power supply with specific characteristics when the sonar functions as a transmitter and a receiver in the specific span time (when on) and the specific lag time (when off). This paper discusses the design of power supply for high-powered sonar systems with discrete methods in which high power supply is only applied when the acoustic waves radiated under water. Charge pump was used to get the appropriate output voltage from lower input voltage. Charge pump utilized a combination of series and parallel connections of capacitors. The working mode of this power supply used the lag time as the calculation of time to charge charge pump capacitors in parallel while the span time was used for the calculation of discharging the charge pump capacitors in series.